PENGARUH PERSEPSI MASYARAKAT TERHADAP KEPUTUSAN MENJADI NASABAH BANK SYARIAH STUDI KASUS PADA MASYARAKAT KOTA SIDOARJO DAN SURABAYA - Komariyah, Fitri; Farhan, Ali (Media Mahardhika, 2020)
Sharia banks are often attached to Muslim communities, causing sharia banks to have an exclusive impression for people to become customers in Sharia banks, as if sharia banks belong to only Muslims. The perception led to the slow development of Sharia banks. This research is trying to understand whether it is true that religious perception affects people to become Sharia bank customers. By using regression analysis, in 156 respondents in the city of Surabaya and Sidoarjo is found that cognitive perception (belief and knowledge), affective (like and dislikes) and contemplative (likelihood) have a positive influence on individual decision to become a customer in Sharia banks.